2023
DOI: 10.1007/s42729-023-01294-4
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Changes and Nutritional Value of Forage Clitoria Grown in Arid Agro-Ecosystem as Influenced by Plant Density and Water Deficit

Abstract: Forage crop productivity has lately reduced in countries located in arid and semi-arid regions worldwide due to intensive consumption and the successive years of drought. This problem is exacerbated by the progress of water scarcity. Thus, the current study is aimed at improving the forage productivity and quality of clitoria as a leguminous fodder crop to be involved in crop rotations under low water supply conditions. As an attempt for facing the drought issue, a two-year (SI and SII) field experiment was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 84 publications
0
6
0
Order By: Relevance
“…The exploration of photosynthesis and its influencing mechanisms under abiotic stress conditions persists as a focal point within plant physiology and ecology (Gao et al, 2018). Previous studies have found that water stress induces stomatal closure, diminishing photosynthetic rates in crop leaves, and consequently inhibiting the biomass accumulation (Makhlouf et al, 2022;Shaaban et al, 2023). The reasons for reduced photosynthetic capacity of plant leaves caused by water deficit are usually attributed to both stomatal and non-stomatal limitations (Wang et al, 2018;Zhang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The exploration of photosynthesis and its influencing mechanisms under abiotic stress conditions persists as a focal point within plant physiology and ecology (Gao et al, 2018). Previous studies have found that water stress induces stomatal closure, diminishing photosynthetic rates in crop leaves, and consequently inhibiting the biomass accumulation (Makhlouf et al, 2022;Shaaban et al, 2023). The reasons for reduced photosynthetic capacity of plant leaves caused by water deficit are usually attributed to both stomatal and non-stomatal limitations (Wang et al, 2018;Zhang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Crops associated with maize inter-and mixed-cropping in the present survey were beans, sorghum, tubers, sunflower, safflower, banana, mango, papaya, avocado, rapeseed, Moringa and others, which are reported to diversify agro-ecosystems in which higher species richness may lower diseases impacts (Terefe et al, 2015), pest outbreaks (Zehnder et al, 2007) and weed infestations (Gudero & Terefe, 2018), hence improving crop productivity (Shaaban et al, 2023).…”
Section: Independent Variable Dfmentioning
confidence: 64%
“…Previous studies have demonstrated that drought stress induces stomatal closure and reduces photosynthetic rates in crop leaves, ultimately inhibiting biomass accumulation [ 24 , 25 ]. Stomatal closure is known to be one of the earliest responses to drought stress in plants [ 26 ].…”
Section: Discussionmentioning
confidence: 99%